Advanced glycation end-products: a common pathway in diabetes and age-related erectile dysfunction. (August 2013) - Neves, D.
Abstract Reactive derivatives of non-enzymatic glucose-protein condensation reactions integrate a heterogeneous group of irreversible adducts called advanced glycation end-products (AGEs). Numerous studies have investigated the role of the AGEs in cardiovascular system; however, its contribution to erectile dysfunction (ED) that is an early manifestation of cardiovascular disease has been less intensively investigated. This review summarizes the most recent advances concerning AGEs effects in the cavernous tissue of the penis and in ED onset, particularly on diabetes and aging, conditions that not only favor AGEs formation, but also increase risk of developing ED. The specific contribution of AGE on intra- and extracellular deposition of insoluble complexes, interference in activity of endothelial nitric oxide (NO) synthase, NO bioavailability, endothelial-dependent vasodilatation, as well as molecular pathways activated by receptor of AGEs are presented. Finally, the interventional actions that prevent AGEs formation, accumulation or activity in the cavernous tissue and that include nutritional pattern modulation, nutraceuticals, exercise, therapeutic strategies (statins, anti-diabetics, inhibitors of phosphodiesterase-5, anti-hypertensive drugs) and inhibitors of AGEs formation and crosslink breakers, are discussed. From this review, we conclude that despite the experiments conducted in animal models pointing to the AGE/RAGE axis as a potential interventional target with respect to ED associated with diabetes and aging, the clinical data have been very disappointing and, until now, did not provide evidence of benefits of treatments directed to AGE inactivation.